Predissociation spectroscopy of cold CN−H2 and CN−D2. (18th August 2022) - Dahlmann, Franziska; Jusko, Pavol; Lara-Moreno, Miguel; Halvick, Philippe; Marimuthu, Aravindh N.; Michaelsen, Tim; Wild, Robert; Geistlinger, Katharina; Schlemmer, Stephan; Stoecklin, Thierry; Wester, Roland; Brünken, Sandra
Abstract : The vibrational predissociation spectra of the CN – H2 and CN – D2 complexes are measured in regions between 450 and 3100 cm − 1 in an ion trap at different temperatures at the free electron lasers for infrared experiments (FELIX) Laboratory. Strong differences between the vibrational spectra of the two para and ortho nuclear spin isomers (CN – (p-H2 ) or CN – (o-H2 ) and CN – (p-D2 ) or CN – (o-D2 )) are detected. In the case of CN – H2 we could assign the observed bands with the help of an accurate quantum calculation. The spectrum is dominated by the first overtone of the hindered H2 rotation in combination with the hindered CN rotation of the CN – (o-H2 ) nuclear spin isomer. The energetically higher-lying CN – (p-H2 ) isomer was not observed due to efficient ortho - para ligand exchange. The C–N stretching mode was recorded at 2040(1) cm − 1 . For the CN – D2 system several vibrational modes of both spin isomers overlap in their low-lying intermonomer streching and bending region, but the main observed bands are attributed to the more stable CN – (p-D2 ) spin isomer. The D–D stretching vibration was found to be at 2898(1) cm − 1 . GRAPHICAL ABSTRACT: UF0001